The Influence of Influencers, Digital Marketing, and Discounts on Purchase Decisions at Sidoarjo Dimsum Shops: Pengaruh Influencer, Digital Marketing, dan Potongan Harga Terhadap Keputusan Pembelian pada Kedai Dimsum Sidoarjo - Priyanti, Nur Laily Dwi; Astuti, Mudji (Indonesian Journal of Law and Economics Review, 2022)
This study aims to detect the influence of influencers, digital marketing, and price discounts on purchasing decisions at Kedai Dimsum Sidoarjo partially or simultaneously. This type of research is a descriptive quantitative research type. This research was conducted at Kedai Dimsum Sidoarjo, which is located on Jalan Sumorame Candi, Sidoarjo Regency. The population in this research are buyers at "Kedai Dimsum Sidoarjo" who have a number that is not recorded with certainty. In taking samples using purposive sampling technique. The number of samples in this research was determined by the Rao formula, which obtained 100 samples. The types of data used are primary and secondary data. In collecting data using a questionnaire method in the form of Google Form. Data were analyzed by multiple liner regression analysis. This study concludes that influencers, digital marketing, and price discounts individually and simultaneously significantly influence purchasing decisions.